Structural and Thermal Insulation Materials Based on High-Strength Anhydrite Binder. Issue 3 (September 2019) - Yakovlev, Grigory; Drochytka, Rostislav; Pervushin, Grigory; Grahov, Valery; Kalabina, Darya; Gordina, Anastasia; Ginchitskaya, Julia
Abstract: The properties of a structural and thermal insulation composition based on a high-strength anhydrite binder based on fluoroanhydrite and expanded perlite sand have been studied. Fluoroanhydrite is a waste product of hydrofluoric acid and it is an eco-friendly material. Due to the processing of man-made anhydrite, it is possible to reduce the harm caused to nature in places of raw materials dumps, as well as significantly reduce the cost of producing new construction materials. The use of anhydrite compounds in the manufacture of products is limited with low speed setting and hardening. To activate the structure formation of the anhydrite binder, 3% aqueous solution of sodium phosphate Na3 PO4 was used. Expanded perlite sand was used as an ultralight aggregate. As a result of the experiments, it was possible to obtain a lightweight composition possessing high strength. Studies of the microstructure and X-ray microanalysis showed new formations appearing in the interfacial zone at the border of the anhydrite binder and expanded perlite, which is confirmed by the results of the infrared spectroscopy. Also there has been noted the consolidation of the anhydrite binder structure by nanodispersed structures formed in the intercrystallite pores of the anhydrite binder. The developed composition can serve as a cheap substitute for gypsum in the production of warm plaster, gypsum boards, architectural elements by molding, tongue-and-groove slabs, wall blocks, as well as wall thermal insulation during frame construction, including for filling hollow masonry.